A double salt of iodobismuthate: cis-aquaiodidobis(1,10-phenanthroline)cobalt(II) tris(1,10-phenanthroline)cobalt(II) trans-hexa-μ(2)-iodido-hexaiodidotribismuthate(III) - Chen, Jiongke (International Union of Crystallography, 2011)
In the title complex, [Co(C(12)H(8)N(2))(3)][CoI(C(12)H(8)N(2))(2)(H(2)O)][Bi(3)I(12)], conventionally abbreviated [Co(phen)(3)][CoI(phen)(2)(H(2)O)][Bi(3)I(12)], where phen is 1,10-phenanthroline, the Co(II) atom in one cation is coordinated by six N atoms from three phen ligands in an octahedral coordination while the Co(II) atom in the other cation is coordinated octahedrally by four N atoms from two phen ligands, one water O atom and one I atom. In the anion, three Bi(III) ions adopt an octahedral coordination constructed by six I(−) ligands. The three BiI(6) octahedra are fused together through trans face-sharing.